Conformational dynamics of superoxide dismutase (SOD1) in osmolytes: a molecular dynamics simulation study. Issue 46 (30th July 2020) - Jahan, Ishrat; Nayeem, Shahid M.
Abstract : Change in conformations of apo and holo SOD1 in water and in osmolytes in terms of configurational entropy ( S ). Abstract : Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease caused by the misfolding of Cu, Zn superoxide dismutase (SOD1). Several earlier studies have shown that monomeric apo SOD1 undergoes significant local unfolding dynamics and is the predecessor for aggregation. Here, we have employed atomistic molecular dynamics (MD) simulations to study the structure and dynamics of monomeric apo and holo SOD1 in water, aqueous urea and aqueous urea–TMAO (trimethylamine oxide) solutions. Loop IV (zinc-binding loop) and loop VII (electrostatic loop) of holo SOD1 are considered as functionally important loops as they are responsible for the structural stability of holo SOD1. We found larger local unfolding of loop IV and VII of apo SOD1 as compared to holo SOD1 in water. Urea induced more unfolding in holo SOD1 than apo SOD1, whereas the stabilization of both the form of SOD1 was observed in ternary solution ( i.e. water/urea/TMAO solution) but the extent of stabilization was higher in holo SOD1 than apo SOD1. The partially unfolded structures of apo SOD1 in water, urea and holo SOD1 in urea were identified by the exposure of the hydrophobic cores, which are highly dynamic and these may be the initial events of aggregation in SOD1. Our simulation studies support the formation of aggregates by means of the local unfolding of monomeric apo SOD1 as compared to holo SOD1 in water.